Factors Affecting the Absorption of Subcutaneously Administered Insulin: Effect on Variability - A. K. J. Gradel; T. Porsgaard; J. Lykkesfeldt; T. Seested; S. Gram-Nielsen; N. R. Kristensen; H. H. F. Refsgaard (Journal of Diabetes Research)
Variability in the effect of subcutaneously administered insulin represents a major challenge in insulin therapy where precise dosing is required in order to achieve targeted glucose levels. Since this variability is largely influenced by the absorption of insulin, a deeper understanding of the factors affecting the absorption of insulin from the subcutaneous tissue is necessary in order to improve glycaemic control and the long-term prognosis in people with diabetes. These factors can be related to either the insulin preparation, the injection site/patient, or the injection technique. This review highlights the factors affecting insulin absorption with special attention on the physiological factors at the injection site. In addition, it also provides a detailed description of the insulin absorption process and the various modifications to this process that have been utilized by the different insulin preparations available.